Moderate and increased physical activity is not detrimental to live birth rates among women with unexplained infertility and obesity - Wendy S. Vitek, M.D; Fangbai Sun, M.P.H; Eden Cardozo, M.D; Kathleen M. Hoeger, M.D., M.P.H; Karl R. Hansen, M.D., Ph.D; Nanette Santoro, M.D; Heping Zhang, Ph.D; Richard S. Legro, M.D (Elsevier, 2023)
Objective: To determine if moderate physical activity is associated with live birth rates in women with unexplained infertility and obesity. Design: Secondary analysis of the Improving Reproductive Fitness through Pretreatment with Lifestyle Modification in Obese Women with Unexplained Infertility trial. Setting: US fertility centers, 2015-2019. Patient(s): A total of 379 women participated in Improving Reproductive Fitness through Pretreatment with Lifestyle Modification in Obese Women with Unexplained Infertility trial, a lifestyle modification program with increased physical activity (phase I, 16 weeks) and up to three cycles of clomiphene citrate treatment and intrauterine insemination (phase II). Intervention(s): Participants were instructed to add 500 steps/day weekly until a maximum of 10,000 steps/day was reached and maintained. Participants were stratified as active (top third, N = 125) and less active (lower third, N = 125) on the basis of the average number of steps per day recorded using a FitBit activity tracker. Main Outcome Measure(s): Live birth rate. Result(s): Active participants were more physically active at the time of enrollment than less active participants (average baseline steps per day, 8,708 [7,079-10,000] vs. 4,695 [3,844-5,811]; P ≤ 0.001) and were more likely to reach 10,000 steps/day than less active participants (average steps per day, 10,526 [9,481-11,810] vs. 6,442 [4,644-7,747]; P ≤ 0.001), although both groups increased their average steps per day by a similar amount (1,818 vs.1,747; P = 0.57). There was no difference in live birth rates (24/125 [19.2%] vs. 25/125 [20%]; P = 0.87) between active and less active participants nor were there differences in clinical pregnancy rates (P = 0.45) or miscarriage rates (P = 0.49) between the two groups. Conclusion(s): Active participants were more likely to achieve the physical activity goal, although this was not associated with benefit or harm with respect to live birth. Clinical Trial Registration Number: ClinicalTrials.gov (NCT02432209), first posted: May 4, 2015.